Ворпо гуждор: 2-5 аресъем нылпиослы лыдзон книга / Вениамин Ившин - Ившин Вениамин Никонорович (Удмуртия, 1997)
Экземпляры: ф. 2 (20210514) / Инвентарный номер: 114048 / Цена: 10.00 / Авт.знак: И 25 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)